Impact of technically qualified surgeons on laparoscopic colorectal resection outcomes: results of a propensity score‐matching analysis. Issue 3 (24th March 2020) - Ichikawa, N.; Homma, S.; Funakoshi, T.; Ohshima, T.; Hirose, K.; Yamada, K.; Nakamoto, H.; Kazui, K.; Yokota, R.; Honma, T.; Maeda, Y.; Yoshida, T.; et al.
Abstract : Background: The Endoscopic Surgical Skill Qualification System (ESSQS) was introduced in Japan to improve the quality of laparoscopic surgery. This cohort study investigated the short‐ and long‐term postoperative outcomes of colorectal cancer laparoscopic procedures performed by or with qualified surgeons compared with outcomes for unqualified surgeons. Methods: All laparoscopic colorectal resections performed from 2010 to 2013 in 11 Japanese hospitals were reviewed retrospectively. The procedures were categorized as performed by surgeons with or without the ESSQS qualification and patients' clinical, pathological and surgical features were used to match subgroups using propensity scoring. Outcome measures included postoperative and long‐term results. Results: Overall, 1428 procedures were analysed; 586 procedures were performed with ESSQS‐qualified surgeons and 842 were done by ESSQS‐unqualified surgeons. Upon matching, two cohorts of 426 patients were selected for comparison of short‐term results. A prevalence of rectal resection (50·3 versus 40·5 per cent; P  < 0·001) and shorter duration of surgery (230 versus 238 min; P  = 0·045) was reported for the ESSQS group. Intraoperative and postoperative complication and reoperation rates were significantly lower in the ESSQS group than in the non‐ESSQS group (1·2 versus 3·6 per cent, P  = 0·014; 4·6 versus 7·5 per cent, P  = 0·025; 1·9 versus 3·9 per cent, P  = 0·023, respectively). These findings were confirmed after propensity score matching. Cox regression analysis found that non‐attendance of ESSQS‐qualified surgeons (hazard ratio 12·30, 95 per cent c.i. 1·28 to 119·10; P  = 0·038) was independently associated with local recurrence in patients with stage II disease. Conclusion: Laparoscopic colorectal procedures performed with ESSQS‐qualified surgeons showed improved postoperative results. Further studies are needed to investigate the impact of the qualification on long‐term oncological outcomes. Abstract : The outcomes of 586 procedures performed or attended by surgeons certified by the Endoscopic Surgical Skill Qualification System (ESSQS) were compared with 842 procedures performed by surgeons without the ESSQS qualification. Attendance of ESSQS‐qualified surgeons led to superior outcomes in terms of duration of surgery, and operative complication and reoperation rates. Non‐attendance of ESSQS‐qualified surgeons was independently associated with local recurrence in patients with stage II disease. Qualification and outcomes in colorectal surgery Abstract : Antecedentes: El Sistema de Certificación de Habilidades Quirúrgicas Endoscópicas ( Endoscopic Surgical Skill Qualification System, ESSQS) fue introducido en Japón para mejorar la calidad de la cirugía laparoscópica. En este estudio de cohortes se investigaron los resultados postoperatorios a corto y a largo plazo de las intervenciones laparoscópicas de cáncer colorrectal realizadas por o con la asistencia de cirujanos con certificación en comparación con cirujanos no certificados. Métodos: Todas las resecciones colorrectales laparoscópicas realizadas entre 2010 y 2013 en 11 hospitales japoneses fueron revisadas retrospectivamente. Los procedimientos se clasificaron en función de si habían sido realizados por cirujanos con o sin certificación del ESSQS, y las características clínicas, patológicas y quirúrgicas de los pacientes se utilizaron para emparejar los subgrupos mediante puntuaciones de propensión. Las variables de resultado incluyeron los resultados postoperatorios y a largo plazo Resultados: En total se analizaron 1.428 procedimientos, incluyendo 586 y 842 procedimientos realizados con y sin cirujanos certificados por ESSQS, respectivamente. Tras el emparejamiento, se seleccionaron dos cohortes de 426 pacientes para la comparación de resultados a corto plazo. Se observó una mayor prevalencia de resecciones rectales (50, 3% versus 40, 1%, P = 0, 0001) y un tiempo quirúrgico más corto (230 versus 238 min, P = 0, 04) en el grupo ESSQS. Las tasas de complicaciones intra‐ y postoperatorias y de reoperaciones fueron significativamente más bajas en el grupo ESSQS que en el grupo no ESSQS (1, 2%, 4, 6% y 1, 9% versus 3, 6%, 7, 5% y 3, 9%, P = 0, 01; 0, 03, y 0, 02, respectivamente). Estos hallazgos se confirmaron tras el análisis de emparejamiento por puntaje de propensión. El análisis de regresión de Cox mostró que la no participación de cirujanos certificados con ESSQS (razón de oportunidades, odds ratio, OR 12, 3; i.c. del 95%, 1, 28–119, 1; P = 0, 03) se asoció independientemente con la recidiva local en los casos en estadio II. Conclusión: Los procedimientos colorrectales laparoscópicos realizados por cirujanos certificados por ESSQS presentaron mejores resultados postoperatorios. Son necesarios más estudios para determinar el impacto de la certificación en los resultados oncológicos a largo plazo.